Evaluation of North Water Spring Ice Cover from Satellite Photographs - Aber,P. G.; Vowinckel,E. (1972)
Satellite photographs for 2 years (March-September) have been used to study ice cover in the polynia called 'North Water', and to determine whether reliable ice maps could be made from satellite data without computer analysis. After early July the clouds become opaque and distinction between cloud and ice is impossible. It was concluded that ice distribution for short periods could best be obtained by careful photograph interpretation. The most persistent open water is found at the northern edge, at about 78 degrees N. The southern ice edge is diffuse. The changes in ice cover in the North are mainly caused by freezing and melting, whereas ice transport is important in the southern area. (Author)